Animal–vehicle collisions in Victoria, Australia: An under‐recognised cause of road traffic crashes. (30th July 2019) - Ang, Jia Ying; Gabbe, Belinda; Cameron, Peter; Beck, Ben
Abstract: Objective: Non‐fatal injuries sustained from animal–vehicle collisions are a globally under‐recognised road safety issue, with limited data on these crash types. The present study aimed to quantify the number and causes of major trauma events resulting from animal–vehicle collisions. Methods: The study was a retrospective analysis of major trauma cases occurring in Victoria, Australia, between 2007 and 2016, using data from the population‐based Victorian State Trauma Registry. To identify animal–vehicle collisions, Victorian State Trauma Registry injury codes were combined with text‐mining of the text description of the injury event. Results: Over the 10 year period, there were 152 major trauma patients who were admitted to Victorian trauma‐receiving hospitals due to vehicle collisions with animals. The crude population‐based incidence rate for animal–vehicle collisions increased by 6.7% per year (incidence rate ratio 1.07; 95% confidence interval 1.01–1.13; P = 0.02). Conclusion: Development of systematic recording methods of animal–vehicle collisions will improve reporting of these crash types to assist future studies in implementing effective countermeasures.